PENGARUH PROMOSI TERHADAP KEPUTUSAN PENGGUNAAN OVO (Studi Pada Mahasiswa Fakultas Ekonomi dan Bisnis Islam IAIN Kediri Angkatan 2016) - Andriani; Indra Nuraini (Istithmar: Jurnal Studi Ekonomi Syariah, 2021)
Experience in payments that are increasingly sophisticated in this era has become a trend in transacting when shopping for goods, paying a service or just paying monthly bills. The choice of payment method makes it easier for us to transact every day. One of them is electronic money. No exception with electronic money service from PT. Visionet International (OVO), they have a strategy in marketing their superior products services including promotions, which is an activity in attracting consumers to use the company's goods or services through the advantages of a product goods or services offered. Where promotions conducted by electronic money service companies (OVO) have an influence on the decision to use their services. This research uses methods with a field research approach. with descriptive quantitative analysis, simple regression analysis, coefficient of determination in interpreting existing phenomena. The results explain that promotion and usage decisions in the category are very good. Pearson's correlation analysis found a score of 0.661. This indicates that the promotional relationship with the purchase decision has a moderate regression relationship. From the results of the regression analysis obtained equation Y = 212.847 + 0.772X; if interpreted has the following meaning in the variable Decision Of Use (Y) will be worth 212,847 if there are no other variables that affect. If there is a Promotion variable (X) intervention, the Usage Decision (Y) variable will increase by 0.772 basis points in each increment. Based on the analysis of determinant coefficients, the value of R-square = 0.4367 (43.67%), which indicates that the Usage Decision (Y) variable in the regression model is capable of being influenced by the Promotion variable (X) of 43.67%, and the remaining 53.33% is influenced by other factors outside the regression model.